Subjetividade, verdade e a problematização ética da docência em Filosofia na contemporaneidade - Ribeiro, Saulo Eduardo (2013)
Departing from studies by Michel Foucault on the historical process of reframing the relationship between subjectivity and truth, this thesis analyzes some possible implications of the requalification of such a relationship in the process of institutionalization and, particularly, the professionalization of philosophy. Thus, this work problematizes the teaching of philosophy in contemporary times based on the analysis of philosophical experience pattern derived from a certain way of conceiving the relationship between subjectivity and truth. In this sense, it can be added to this historical research, especially this one mapped out by recent studies by Foucault, the analysis of the literature on teaching and on philosophy teaching. Starting from the historical investigation of how the philosophical practice has worked and happened, we seek to present the boundaries of this practice by putting it to the test of the present in which we live. Inserting the philosophical practice and experience in the historical dimension to which it is related, we intend to put it in the order of questioning what we have recognized so far as necessary with respect to its exercise. Problematizing the need of the relationship we have established between what a particular tradition has conceived as philosophy and / or philosophical practice and what has been done in relation to this tradition in educational institutions, we intend to draw a ―strategic map‖ so that we can think of other possibilities in which philosophy will work and happen differently. Assuming that there is not a necessary, but a historical relationship between what is conceived as philosophy and what we do and think in relation to it, we intend to subscribe the philosophical practice under another order, not that one linked to theoretical problematization, but the one linked to ethical issues. This way, we discuss the situation of philosophy in schools considering the collapse of experience patterns in modernity, the subjectivity process involved in philosophical practice in relation to the production process of modern standardized subject, as well as the (im)possibilities of philosophy constitute itself a philosophical experience in school with the collapse of these patterns. Therefore, with this study, we aim at visualizing some alternative for the teaching of Philosophy that enables, from an immanent ethics and aesthetics, other forms of subjectivity production to the teachers and thus another possibility of getting related to the truth.